Implementasi Data Mining Algoritma Apriori Pada Sistem Persediaan Bahan Bangunan Di Karang Sari - Zahra Syahara; Rika Nur Adiha; Agus Perdana Windarto (LPPM STIKOM Tunas Bangsa, 2021)
The development of construction in Indonesia is increasing rapidly, therefore building materials are needed to be used in building a construction. Every building materials store must have a transaction system and an inventory system. Whether it's an efficient or less efficient inventory system. For this reason, this research was conducted to help the owner or manager of a building shop to more easily determine the combination pattern of supplies and purchases of building goods. The a priori algorithm is used in this study because the a priori algorithm is suitable in connecting the itemset combination patterns. Therefore the a priori algorithm is suitable in determining the purchase combination pattern in order to get a good inventory system. And from the process carried out, a confidence value of 75% was obtained, not only that this research was also assisted by a priori algorithm supporting application, namely the Tanagra application.